An investigation of some differences between aspects in hill country : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science at Massey University - Lambert, Matthew Greg (Massey University, 1973)
Climatic, edaphic and biotic variables were measured, over a twelve month period, at each of four aspects of a hill in the Southern Ruahine ranges. These variables were soil moisture status, soil temperature, air temperature, wind-speed, rainfall, soil nutrient status, sheep-dung deposition, and pasture botanical composition and productivity. Information on sunshine hours, maximum and minimum screen temperatures, relative humidity, and wind direction were obtained from the records of an adjacent meteorological station. Net radiation and potential evapotranspiration were calculated from meteorological data, and actual evapotranspiration from soil moisture data. Large differences were recorded between aspects for most of the above mentioned variables. The wind during the observational period was a prevailing West/Northwesterly. Differences in net radiation between the north and south aspects were largest during the Winter and smallest during the summer months. In all cases the evapotranspiration values calculated were larger for the north than for the south aspect. Soil moisture tension differences were not detected during the winter months, but during the remainder of the year the north aspect was driest, followed by the east and west aspects, and the south aspect respectively Differences between aspects, in terms of average monthly 4 cm. air temperature, were not apparent. However, large differences in the average monthly 4 cm. soil temperature of the various aspects were detected: during the January to August period the north aspect was warmest and the south coolest; during the October to December period the east aspect was warmest and the north and south aspects, which had similar average soil temperatures, were coolest. The south and west aspect soils had greater nutritional limitations to plant growth than did the soils of the east and north aspects. This was probably due, at least in part, to nutrient transfer by grazing animals, and the differential action of soil-forming factors. Nitrogen mineralisation was closely associated with soil total nitrogen status, and was one of the main factors limiting pasture productivity. Soil moisture status was the other major limitation to pasture productivity. Pasture production during the observational period (346 days), for the east, south, west and north aspects respectively, was 9683, 3637, 2959 and 2771 kg./DM./ha. Some of the pasture species present were found to be distributed in a definite pattern according to aspect, while for other species the pattern was indistinct. For a number of species no distribution pattern was detected. The patterns observed appeared to follow soil nutritional (especially mineral nitrogen) and soil moisture gradients. Possible reasons for the above-mentioned differences, and some practical implications of these differences, are discussed.
Keywords: Agricultural Meteorology; Plant ecology; Pastures -- Effect of climate on